LEARNING WITH HEART: HOW TO LOVE THE PROCESS, NOT JUST THE RESULT - Mahmudova Maftunakhon Mahmud kizi (Bright Mind Publishing, 2025)
This thesis investigates the emotional, cognitive, and philosophical underpinnings of process-based learning as a vital alternative to outcome-driven educational models. In a world that frequently prioritizes performance metrics and quantifiable results, learners are often conditioned to pursue external validation over genuine intellectual engagement. Drawing upon psychological theories of intrinsic motivation, emotional intelligence, and learner autonomy—as well as philosophical perspectives from Dewey and Freire—this work argues that sustainable, transformative learning arises not from the pursuit of achievement, but from a cultivated affection for the learning process itself. It asserts that to love the journey is to humanize education and reframe it as a lifelong act of becoming.
Keywords: Intrinsic motivation, process-oriented learning, emotional intelligence, learner autonomy, cognitive engagement, self-determination theory, pedagogical transformation, experiential education, reflective practice, existential learning.